Effectiveness of Biochar for Sorption of Ammonium and Phosphate from Dairy Effluent. Issue 5 (1st September 2013) - Sarkhot, D. V.; Ghezzehei, T. A.; Berhe, A. A.
Abstract : The use of biochar for recovery of excess nutrients in dairy manure effluent and the use of nutrient‐enriched biochar as soil amendment can offer a robust solution for multiple environmental issues. In this study we determined the capacity of biochar, produced by pyrolyzing mixed hardwood feedstock at 300°C, to adsorb and retain or release two major nutrient ions: ammonium (NH4 + ) and phosphate (PO4 3− ). We conducted the experiment using a range of nutrient concentrations that represent those commonly observed in dairy manure effluent (0–50 mg L −1 for PO4 3− and 0–1000 mg L −1 for NH4 + ). Up to 5.3 mg g −1 NH4 + and 0.24 mg g −1 PO4 3− was adsorbed from manure by biochar (18 and 50% of total amount in the manure slurry, respectively). During the desorption phase of the experiment, biochar retained 78 to 91% of the sorbed NH4 + and 60% of the sorbed PO4 3− at reaction times <24 h. Our findings confirm that biochar can be used for recovering excess nitrogen and phosphorus from agricultural water, such as dairy manure effluent.